'Now it was meal'. (9th December 2021) - Björk-Willén, Polly
Abstract : The overall aim of the present paper is to analyse and explore what frames a pretend play event as legal and recognizable to the participants, highlighting the children's use of tense as an organizational device. The present video data are drawn from a single case study of two preschoolers' interaction during a free play time event in a Swedish preschool. Influenced by ethnomethodological work on social actions, the analytical focus is on the participants' methods of accomplishing and making sense of social activities. The use of tense proved to be the strongest contextualization cue to accomplish the switches between the 'make believe' and 'the real' domains, which demonstrated and organized what can and cannot be done in the pretend play scenario.